Omvendelse og modvilje - Engberg, Jakob (Religionsvidenskabeligt Tidsskrift, 1997)
When pagans met Christians or Christianity, this meeting could produce a variety of different reactions or feelings. Some were attracted by what they saw or heard, while others were disgusted. Some were filled with fear or simply annoyed, while others were indifferent, and others again might have had a mixture of conflicting feelings. These different reactions to Christianity in some cases resulted in either conversion or aversion. The object of the article has been to explain these two reactions. An analysis of pagan attitudes towards ungodliness (atheos) and superstition (superstitio or deisidaimonios) notably of Plutarch's De superstitione has formed the basis of my argument. I have argued that some saw Christianity or Christians as ungodly or superstitious and that this could produce aversion. On the other hand, I have argues, inspired by Plutarch, that others in Christianity saw a liberation from superstition, and that this could contribute to conversion.